Modification of highly dispersed silica with palladium acetylacetonate to obtain new catalysts for hydrogen oxidation with oxygen - M. V. Borysenko; O. Yu. Boldyrieva; V. V. Lisnyak (Хімія, фізика та технологія поверхні, 2025)
Palladium (Pd) catalysts for the hydrogen recombination (low-temperature oxidation of hydrogen with oxygen) have been prepared and studied. These catalysts should prevent the risk of explosions of hydrogen-containing air mixtures and fires during accumulation of hydrogen in confined technological spaces, the source of which are leaks in enterprises using hydrogen or accidents during operation of water-water reactors. The developed palladium-containing catalysts on highly dispersed silica allow to recombine effectively hydrogen leaks (with the participation of air oxygen) and prevent their accumulation in a confined volume. For all the catalysts studied, in the first heating and cooling cycle in a reaction gas mixture consisting of 1 vol. % hydrogen and 20 vol. % oxygen diluted with argon, a temperature hysteresis is observed on the curves of dependence of the degree of hydrogen conversion, which disappears in the second heating and cooling cycle when the catalyst is treated in the reaction gas mixture. A decrease in catalytic activity with increasing Pd content is determined for catalysts obtained by the gas-phase method, by treating highly dispersed silica with Pd(acac)2 vapor at 120 °C. This effect can be explained by the size factor. This implies a cluster coverage of the surface of highly dispersed silica as a support of Pd metal complexes grafted to the surface by the gas-phase method. After thermal decomposition of the formed surface Pd-acetylacetonate complexes, the obtained catalysts show a significant increase in catalytic activity with increasing Pd content, which is inherent to supported metallic catalysts. Among the obtained Pd catalysts, a sample with a Pd concentration of 0.03 wt. % in the composition of grafted highly dispersed Pd monoacetylacetonate is the most economical in terms of production and application, since due to the saving of palladium while maintaining a high catalytic activity at room temperature, it is the best alternative to more expensive commercial catalysts.